Ohmygadget Computer IT Service and Maintenance System - Noor Baharim, Noor Raihanah; Mohd Yunus, Mohd Amin (Applied Information Technology And Computer Science, 2025)
In today's digital world, where technology is deeply integrated into every facet of life, a reliable computer IT service system is no longer a luxury, but a necessity. This study researches the development of a web-based system using PHP language and MySQL. The system empowers users to submit service requests, track service progress in real-time, and access updates readily. Moreover, automated background tasks, encompassing report generation and client notifications, enhance workflow efficiency. Employing the agile methodology, the system undergoes continuous improvement through iterative cycles, incorporating valuable user feedback to refine functionality and adapt to evolving demands. The research findings reveal significant improvements in service efficiency, enhanced user transparency, and increased user satisfaction. Future research aims to explore the integration of advanced features, such as remote diagnostics and preventative maintenance, further optimizing IT service delivery and solidifying the system's position as a valuable tool for IT teams to ensure seamless and efficient service. A computer IT service system acts as a safety net, ensuring the smooth operation and security of essential technology. Therefore, investing in a robust computer IT service system is an investment in your present and future success. It protects valuable data, ensures optimal performance, and allows technology to its full potential, ultimately contributing to a more productive and secure digital environment.